EFL Teachers' Perceptions in LMS-Mediated Blended Classrooms: Insights from a Non-Formal Junior High School - Fauziah, Nurul Isra; Merysa (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2025)
This research aims to explore English as Foreign Language (EFL) teachers’ perception of  synchronous activities, both web-assisted and face-to-face, within Learning Management System (LMS)-facilitated blended classrooms. This study examined the advantages and disadvantages of the different modes of synchronous activities from the teachers’ point of view. A qualitative case study was used in this study, focusing on a non-formal junior high school in Indonesia which implemented a blended learning post Covid era. The data was collected through semi-structured interviews. The findings reveal that web-assisted sessions offer flexibility, accessibility, and inclusivity, fostering student independence and confidence. However, they also present challenges related to classroom management, technical issues, and limited teacher control over student engagement. Conversely, face-to-face sessions provide a more controlled learning environment and allow for immediate feedback, yet some students become overly reliant on teacher guidance and neglect independent learning via the LMS.  This research contributes new perspectives to blended learning, particularly by highlighting the unique implementation and pedagogical challenges in a non-formal junior high school setting following the Covid-19 pandemic.